Photonic devices and systems - Hunsperger, Robert G. (Optical engineering (Marcel Dekker, Inc.), 1994)
This work describes all the major devices used in photonic systems. It provides a thorough overview of the field of photonics, detailing practical examples of photonic technology in a wide range of applications. Photonic systems and devices are discussed with a mathematical rigor that is precise enough for design purposes yet highly readable.